Proverb comprehension deficits in patients with schizophrenia - Mohnke, Margaux; Bach, Claudia; Roesch-Ely, Daniela (Zeitschrift für Neuropsychologie, 2019)
Patients suffering from schizophrenia typically show difficulty comprehending proverbs. This deficit has been linked to social and neurocognitive domains, such as theory of mind (TOM) and, more recently, working memory (WM). It is still unclear which cognitive deficits underlie proverb comprehension. We analyzed possible associations of proverb comprehension to neurocognitive and social cognitive dysfunctions in 64 patients with schizophrenia spectrum disorders, by combining tests measuring executive functions (inhibition, cognitive flexibility, planning), WM (verbal and visuo-spatial), and social cognition (TOM). A hierarchical regression demonstrated that WM and executive dysfunction best predicted proverb comprehension, which in turn supports the conceptual integration model. Social cognition showed no additional predictive value. The ability to comprehend figurative language might depend more on neurocognitive than on social cognitive abilities.
Gesehen am 16.04.2020